2021
DOI: 10.3126/mjmms.v1i1.42951
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication Practice in Primary Dysmenorrhea among Nursing Students: A Cross Sectional Study

Abstract: INTRODUCTION: Self-medication and home remedies are most commonly employed for relief from menstrual discomfort in female students. Self-medication practice varies among adolescent female students. Hence, this study aims to observe and analyze self-medication practice and drugs used for primary dysmenorrhea among nursing students. MATERIALS AND METHODS: This cross sectional study was conducted at Janaki Medical College and College of Nursing, Sinha Health Foundation, Dhanusha from October 2019 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…But our finding indicated that majority (78.57%) of students used to take these medications when pain started indicating the need for professional consultation. Mefenamic acid was the most common used analgesic by the majority of the students (90.48%) for dysmenorrhea and this finding was similar to the report of Chaurasia et al 30 In contrast to this, mefenemic acid+dicyclomine (67.4%) was the most common used analgesic by the students in a study by Jayanthi et al 36 More than one-third of the students (30.95%) were not able to mention the correct dose of the analgesic drug they were using and majority of them (90.48%) were also not able to mention the correct frequency of the drug intake. This unsafe practice of self-medication might have serious implications including harm to themselves and a constant risk of medication error.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…But our finding indicated that majority (78.57%) of students used to take these medications when pain started indicating the need for professional consultation. Mefenamic acid was the most common used analgesic by the majority of the students (90.48%) for dysmenorrhea and this finding was similar to the report of Chaurasia et al 30 In contrast to this, mefenemic acid+dicyclomine (67.4%) was the most common used analgesic by the students in a study by Jayanthi et al 36 More than one-third of the students (30.95%) were not able to mention the correct dose of the analgesic drug they were using and majority of them (90.48%) were also not able to mention the correct frequency of the drug intake. This unsafe practice of self-medication might have serious implications including harm to themselves and a constant risk of medication error.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to this, lower percentage of the students practiced self-medication in other studies. 9,29,30 Fatima et al had reported a high prevalence (62.98%) of self-medication in dysmenorrhea. 31 These difference might be due to difference in knowledge level of analgesics, availability of drugs and extent of perceived difficulty of painful menses.…”
Section: Discussionmentioning
confidence: 99%
“…These percentages differ from Chaurasia et al study, where self-medication was observed in 35.20% and only 4.70% took prescribed medicines. 18 These differences in percentages suggest potential variations in cultural or demographic factors influencing healthcare-seeking behaviours for menstrual pain. Further research is needed to understand these differences and develop targeted interventions for menstrual pain and healthcare-seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmenorrhea accounts for an estimated 140 million missed work or school days each year. As a result, home remedies and self-medication with NSAIDs, naproxen sodium, and mefenamic acid are the most common methods used by women to alleviate menstrual discomfort [3][4][5]. Te American College of Obstetricians and Gynecologists (ACOG) defnes dysmenorrhea as the "pain associated with menstruation."…”
Section: Background Of the Studymentioning
confidence: 99%